THE ROLE OF THE FEDERAL SYSTEM ON THE STRUCTURE AND OPERATION OF POLITICAL PARTIES IN ETHIOPIA - Abeje, Alefe (European Scientific Journal, ESJ, 2014)
Federalism in Ethiopia has contributed for the democratization process by giving due consideration to the hitherto marginalized groups and by addressing the country’s age-old problem of national question. The adoption of the federal system of government was meant to provide a proper balance between the centre and regions. In principle, the multiparty system strengthens the functioning of federal structures in a democratic society. The division of power at different levels of government can be made more equitable and fair in a country with competitive party system. However, in Ethiopia, contrary to this well-established principle, there is a strong centralised party with overarching control of government at all levels of government. Besides, there is a lack of clear line between party and state. These, together with lack of strong opposition parties, are against the existence of a genuine federal system. Although it is positive that all the parties recognised the need to maintain the federal system, in practice opposition political parties have stand against some of the major pillars of the system such as the ethnic component of the federal system and right of ethnic groups to selfdetermination up to secession.